Customer behavior towards online shopping / Azni Syafena Andin Salamat...[et al.] - Andin Salamat, Azni Syafena; Ali, Norhidayah; Mohamed Isa, Zuraidah (2010)
Internet has become a part of our daily life. Some may agree that the internet offers convenience and benefit by accelerating their daily transactions such as on-line banking, on-line shopping and other online transactions. In addition, internet shopping provides a lot of information regarding a product. Such information may help internet shoppers in deciding buying a right product at the right cost. Online shopping is totally different from a traditional shopping. In the traditional shopping, the customers will inspect the goods or services and evaluate the manufacturer or vendor before making the purchase. In contrast, for online shopping, customers are not guaranteed to receive the exact products or services according to the description and image on the computer screen. Online shopping also requires customer to share personal details, financial information and they might suffered from the issues of privacy where their information are easily accessible. This paper attempts to identify dimensions affecting customer behavior on online shopping. Some recommendations will also be provided in the paper for further improvement.